Ceramide and sphingosine 1-phosphate in adipose dysfunction. (April 2019) - Fang, Zijian; Pyne, Susan; Pyne, Nigel J.
Abstract: The increased adipose tissue mass of obese individuals enhances the risk of metabolic syndrome, type 2 diabetes and cardiovascular diseases. During pathological expansion of adipose tissue, multiple molecular controls of lipid storage, adipocyte turn-over and endocrine secretion are perturbed and abnormal lipid metabolism results in a distinct lipid profile. There is a role for ceramides and sphingosine 1-phosphate (S1P) in inducing adipose dysfunction. For instance, the alteration of ceramide biosynthesis, through the de-regulation of key enzymes, results in aberrant formation of ceramides (e.g. C16:0 and C18:0 ) which block insulin signaling and promote adipose inflammation. Furthermore, S1P can induce defective adipose tissue phenotypes by promoting chronic inflammation and inhibiting adipogenesis. These abnormal changes are discussed in the context of possible therapeutic approaches to re-establish normal adipose function and to, thereby, increase insulin sensitivity in type 2 diabetes. Such novel approaches include blockade of ceramide biosynthesis using inhibitors of sphingomyelinase or dihydroceramide desaturase and by antagonism of S1P receptors, such as S1P2 .